Investigating Effects of Sex Differences and Prior Concussions on Symptom Reporting and Cognition Among Adolescent Soccer Players. Issue 4 (March 2018) - Brooks, Brian L.; Silverberg, Noah; Maxwell, Bruce; Mannix, Rebekah; Zafonte, Ross; Berkner, Paul D.; Iverson, Grant L.
Background: There has been increasing concern regarding the possible effect of multiple concussions on the developing brain, especially for adolescent females. Hypothesis/Purpose: The objectives were to determine if there are differences in cognitive functioning, symptom reporting, and/or sex effects from prior concussions. In a very large sample of youth soccer players, it was hypothesized that (1) there would be no differences in cognitive test performance between those with and without prior concussions, (2) baseline preseason symptoms would be better predicted by noninjury factors than concussion history, and (3) males and females with prior concussions would not have differences in cognition or symptoms. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Participants included 9314 youth soccer players (mean = 14.8 years, SD = 1.2) who completed preseason baseline cognitive testing, symptom reporting, and a health/injury history questionnaire from the ImPACT battery (Immediate Post-concussion Assessment and Cognitive Testing). On the basis of injury history, athletes were grouped by number of prior concussions: 0 (boys, n = 4012; girls, n = 3963), 1 (boys, n = 527; girls, n = 457), 2 (boys, n = 130; girls, n = 97), or ≥3 (boys, n = 73; girls, n = 55). The primary measures were the 4 primary cognitive scores and the total symptom ratings from ImPACT. Primary outcomes were assessed across injury groups, controlling for age, sex, learning disability, attention-deficit/hyperactivity disorder (ADHD), treatment for headaches/migraines, substance abuse, and mental health problems. Results: Cognitive test performance was not associated with concussion history but was associated with sex, age, learning disability, ADHD, and prior mental health problems. Greater symptom reporting was more strongly associated with psychiatric problems, older age, learning disability, substance abuse, headaches, being female, and ADHD than with a history of multiple concussions. Boys and girls did not differ on cognitive scores or symptom reporting based on a history of concussion. Conclusion: In this very large sample of youth soccer players with prior concussion, there was no evidence of negative effects on cognition, very weak evidence of negative effects on symptom reporting, and no evidence of sex × concussion differences in cognition or symptom reporting.